SPIRITUAL VIRTUUM: THE INTERACTION OF THE FINITE AND THE INFINITE - Kharchenko, Julia; Kharchenko, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
The virtuum is shown as one of the dimensions of society. The conceptualization of the phenomenon of the spiritual virtuum in the context of the interaction of the virtuum infinite in being and finite in the digital reality of the cyber-techno-sphere is the goal of this study. The phenomenon of the virtuum is considered within the framework of socio-philosophical, ontological, and transcendental approaches. Each virtual object is finite and discontinuous. In the spiritual virtuum the boundary is conditional and imaginary. The position is summarized that a computer designer who is able to adapt to various life situations, in order to manage virtual reality. The spiritual virtuum or the peculiar life of the Digital Spirit can be understood as a property of the soul, consisting in the predominance of spiritual, moral, and intellectual interests over material ones.